2011
DOI: 10.1007/s11095-011-0403-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterisation of Bioadhesive PLGA/Chitosan Microparticles Produced by Supercritical Fluid Technology

Abstract: The strong interaction of mucin with the chitosan present on the surface of the particles suggests a potential use of the mucoadhesive carriers for gastroretentive and oral controlled drug release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The research proved that after intravenous injection, grain size at 7~30 μm can be mechanically intercepted by capillary bed and then accumulate in the lungs. Casettari and others found that positively charged particles and reach lungs easily [25]. The microspheres made by this research had an average grain diameter of 9.6 μm.…”
Section: Resultsmentioning
confidence: 69%
“…The research proved that after intravenous injection, grain size at 7~30 μm can be mechanically intercepted by capillary bed and then accumulate in the lungs. Casettari and others found that positively charged particles and reach lungs easily [25]. The microspheres made by this research had an average grain diameter of 9.6 μm.…”
Section: Resultsmentioning
confidence: 69%
“…For example, protein loaded lipid micro particles were produced and reported by Salas et al [23]. Casettari et al report the use of PASS for the development of mucoadhesive particles form chitosan and poly-lactic acid for gastrointestinal drug delivery [24]. Falconer et al present a multivariate study on the effect of different operating conditions for the preparation of progesterone loaded gelucire particles and the results demonstrate that not only the independent variables of pressure and temperature influence the result but also the interaction between them influence the yield of the process [25].…”
Section: Particle Formation/encapsulationmentioning
confidence: 99%
“…Under these conditions, the Maillard reaction took place as well. Biodegradable and mucoadhesive PLGA/chitosan microparticles were manufactured by Casettari et al [104] by using scCO 2 with the addition of mPEG and chitosan in the absence of organic solvents, surfactants and crosslinkers. Analytical surface techniques, along with the interaction with mucin, demonstrated the presence of the chitosan (<100 μm) on the surface of the particles.…”
Section: Supercritical Dryingmentioning
confidence: 99%